Evaluating the effects of CO2 capture benchmarks on efficiency and costs of membrane systems for post-combustion capture: A parametric simulation study. (August 2017) - Giordano, Lorena; Roizard, Denis; Bounaceur, Roda; Favre, Eric
Abstract: Membrane separation is considered to be the most promising alternative to chemical absorption for decarbonizing fossil fuel power generating systems. However, the implementation of a membrane system has several implications for the energy and economic performances of power plants. Indeed, membrane systems allow for the non-negligible reduction of power plant capacity, which can negatively affect its efficiency. This aspect, combined with the additional capital and operating expenses, is also responsible for an increase in the electricity generation costs. Currently, the majority of studies neglected to investigate the influence of CO2 separation targets on costs, thus limiting their investigation to the case of geological storage or enhanced oil recovery (EOR) that mean CO2 purity levels after compression higher than 95%. But for certain valorization aims, like CO2 hydrogenation or solar thermochemical conversion, lower CO2 quality standards may be sufficient; to the best of our knowledge there is currently no study allowing to know the cost of CO2 capture in this unusual framework. The aim of this paper was to analyze the effects of CO2 purity targets on the energy requirement for the separation and compression operations and costs of membrane systems, considering as a study case the recovery of CO2 from flue gases of a coal-fired power plant and using a Polyactive membrane. The CO2 separation process was first investigated by exploring several membrane system concepts. Then, by focusing on dual-stage configurations, the entire carbon capture and storage (CCS) chain was analyzed. From an energy view point, the study quantified the impact of CO2 capture retrofit intervention on the power plant's net efficiency and the extent of CO2 emissions reduction. Besides, the economic analysis allowed for an evaluation of the specific cost of the CO2 capture and the mitigation cost with or without credits for EOR. Finally, an energy and economic comparison was made with the CO2 capture based on chemical scrubbing. With a CO2 separation cost of 20÷33 $/tonne, a single stage membrane system with feed compression and permeate vacuum pumping represents the most interesting option to be used in combination with CO2 recycling technologies requiring a medium-low CO2 purity level (70÷80%). Simulation results also revealed that dual stage membrane systems envisaged are economically competitive compared to amine absorption processes in the case of geological storage, involving a cost of CO2 capture of 36÷41 $/tonne.